Factors associated with suboptimal adherence to antiretroviral therapy in Asia. Issue 2 (16th May 2014) - Jiamsakul, Awachana; Kumarasamy, Nagalingeswaran; Ditangco, Rossana; Li, Patrick CK; Phanuphak, Praphan; Sirisanthana, Thira; Sungkanuparph, Somnuek; Kantipong, Pacharee; Lee, Christopher KC; Mustafa, Mahiran; Merati, Tuti; Kamarulzaman, Adeeba; et al.
Abstract : Introduction: Adherence to antiretroviral therapy (ART) plays an important role in treatment outcomes. It is crucial to identify factors influencing adherence in order to optimize treatment responses. The aim of this study was to assess the rates of, and factors associated with, suboptimal adherence (SubAdh) in the first 24 months of ART in an Asian HIV cohort. Methods: As part of a prospective resistance monitoring study, the TREAT Asia Studies to Evaluate Resistance Monitoring Study (TASER‐M) collected patients' adherence based on the World Health Organization‐validated Adherence Visual Analogue Scale. SubAdh was defined in two ways: (i) <100% and (ii) <95%. Follow‐up time started from ART initiation and was censored at 24 months, loss to follow‐up, death, treatment switch, or treatment cessation for >14 days. Time was divided into four intervals: 0–6, 6–12, 12–18 and 18–24 months. Factors associated with SubAdh were analysed using generalized estimating equations. Results: Out of 1316 patients, 32% ever reported <100% adherence and 17% ever reported <95%. Defining the outcome as SubAdh <100%, the rates of SubAdh for the four time intervals were 26%, 17%, 12% and 10%. Sites with an average of >2 assessments per patient per year had an odds ratio (OR)=0.7 (95% confidence interval (CI) (0.55 to 0.90), p =0.006), compared to sites with ≤2 assessments per patient per year. Compared to heterosexual exposure, SubAdh was higher in injecting drug users (IDUs) (OR=1.92, 95% CI (1.23 to 3.00), p =0.004) and lower in homosexual exposure (OR=0.52, 95% CI (0.38 to 0.71), p <0.001). Patients taking a nucleoside transcriptase inhibitor and protease inhibitor (NRTI+PI) combination were less likely to report adherence <100% (OR=0.36, 95% CI (0.20 to 0.67), p =0.001) compared to patients taking an NRTI and non‐nucleoside transcriptase inhibitor (NRTI+NNRTI) combination. SubAdh decreased with increasing time on ART (all p <0.001). Similar associations were found with adherence <95% as the outcome. Conclusions: We found that SubAdh, defined as either <100% and <95%, was associated with mode of HIV exposure, ART regimen, time on ART and frequency of adherence measurement. The more frequently sites assessed patients, the lower the SubAdh, possibly reflecting site resourcing for patient counselling. Although social desirability bias could not be excluded, a greater emphasis on more frequent adherence counselling immediately following ART initiation and through the first six months may be valuable in promoting treatment and programme retention.